Impact of atrial fibrillation catheter ablation on mortality, stroke, and heart failure hospitalizations: A meta‐analysis. (9th March 2020) - Saglietto, Andrea; De Ponti, Roberto; Di Biase, Luigi; Matta, Mario; Gaita, Fiorenzo; Romero, Jorge; De Ferrari, Gaetano M.; Anselmino, Matteo
Abstract: Background: The impact of atrial fibrillation catheter ablation (AFCA) on hard clinical endpoints remains controversial. Objective: Our aim was to conduct a random‐effect model meta‐analysis on efficacy data from high‐quality large matched database/registry studies and randomized clinical trials. We compared long‐term all‐cause mortality, stroke, and hospitalization for heart failure in patients undergoing AFCA vs patients treated with medical therapy alone (rhythm and/or rate control medications) in a general AF population. Methods and Results: PubMed/MEDLINE and Embase databases were screened and a total of nine studies were selected (one randomized clinical trial—CABANA—and eight large matched population studies). A total of 241 372 patients (27 711 in the ablation group, 213 661 in the nonablation group) were included. After a median follow‐up of 3.5 years, AFCA decreased the risk of mortality (hazard ratio [HR], 0.62; 95% confidence interval [CI], 0.54‐0.72; I 2 = 54%; number needed to treat [NNT] = 28), stroke (HR, 0.63; 95% CI, 0.56‐0.70; I 2  = 23%; NNT = 59) and hospitalization for heart failure (HR, 0.64; 95% CI, 0.51‐0.80; I 2  = 28%; NNT = 33) compared with AF patients treated with medical therapy alone. Conclusion: Based on the currently available efficacy and effectiveness evidence, AFCA significantly reduces the risk of death, stroke, and hospitalization compared with medical therapy alone.